QADHRU HASAN SEBAGAI MEDIA DALAM MEMBANGUN COSTUMER LOYALTY PADA KOPERASI JASA KEUANGAN SYARIAH - Hamzah, Muh; Rahayu, Rizky Indah (JURNAL ISLAM NUSANTARA, 2021)
This study aims to analyze and understand the efforts made by BMT NU Besuki Branch in building Customer Loyalty through Qadhru Hasan. This research uses a qualitative case study approach. The data collection technique is done through participant observation, interviews, and documentation. The data analysis was carried out through the stages of data presentation, data reduction, and concluding. The results showed that Qadhru Hasan in building customer loyalty at BMT NU Besuki Branch through a mature strategy and paying attention to technological advances to excel in the competition and increase customer loyalty, including present a gift for customers, customer service oriented to customer satisfaction, and visiting customers. This research has implications for the importance of building excellent service for an organization, both services and business heads of customers, to be able to provide satisfaction for them